PENGARUH KONSENTRASI EKSTRAK KULIT JERUK NIPIS (Citrus aurantifolia S.) TERHADAP KEPADATAN POPULASI DAN INTENSITAS SERANGAN Plutella xylostella L. (LEPIDOPTERA : PLUTELLIDAE) PADA TANAMAN KUBIS - Moh Hiban Toana (Universitas Tadulako, 2007)
The research aim was to identify the influence of extract concentration of orange skin on the population density andthe attack intensity of the larvae P. xylostella. The research was conducted from June to September 2004 in Bobo Village,Palolo Regency, Donggala District, Province of Central Sulawesi. The research used a Completely Randomized Design with 5treatments replicated 3 times, thus, there were 15 experimental units. The levels of extract concentrations were without extractas a control (A), 10% extract concentration (B), 20 % extract concentration (C), 40 % extract concentration (D), and 80%extract concentration (E). The research results showed that the extract of orange skin significantly decreased the population ofthe P. xylostella larvae. The best treatment was the 80 % extract concentration than other application.Keywords: Extract skin of orange, population density, attack intensity, and P. xylostell